The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3168/jds.2019-17359
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Milk microbiota profiling on water buffalo with full-length 16S rRNA using nanopore sequencing

Abstract: The identification of milk microbial communities in ruminants is relevant for understanding the association between milk microbiota and health status. The most common approach for studying the microbiota is amplifying and sequencing specific hypervariable regions of the 16S rRNA gene using massive sequencing techniques. However, the taxonomic resolution is limited to family and, in some cases, genus level. We aimed to improve taxonomic classification of the water buffalo milk microbiota by amplifying and seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
(44 reference statements)
0
14
0
1
Order By: Relevance
“…Although differential taxonomy profiles of clinical samples were shown at the genus or species levels using two different bioinformatics analyses in this study, the setting or workflow and employed reference were highly relevant to the identified results of MinION sequencing. For EPI2ME, the employed parameter involved in implementation of the algorithm was absent, which might be considered a “black box” [ 23 , 24 ]. More related research is required to polish the accuracy of error-prone long reads against distinct reference databases.…”
Section: Discussionmentioning
confidence: 99%
“…Although differential taxonomy profiles of clinical samples were shown at the genus or species levels using two different bioinformatics analyses in this study, the setting or workflow and employed reference were highly relevant to the identified results of MinION sequencing. For EPI2ME, the employed parameter involved in implementation of the algorithm was absent, which might be considered a “black box” [ 23 , 24 ]. More related research is required to polish the accuracy of error-prone long reads against distinct reference databases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, targeting the full-length SSU rRNA gene helps to identify bacteria, archaea, and eukaryotes at improved taxonomic levels. For instance, Catozzi et al [17] published a full-length 16S rRNA sequencing strategy for the milk microbiota of water buffalos. In this study, the authors demonstrated that full-length strategies are suitable for species-level detection.…”
Section: Using Full-length Sequencing Approaches For Microbial Monitoringmentioning
confidence: 99%
“…The sequencing of milk samples using short amplicon sequencing was performed intensively before, e.g., by Porcellato et al [7], Taponen et al [8], Metzger et al [9], Cremonesi et al [10], Metzger et al [11], Pang et al [12], Doyle et al [13], Oultram et al [14], Sokolov et al [15] and Li et al [16]. Nevertheless, full-length sequencing approaches are rare and, if published, are mostly performed using long-read sequencers, e.g., Catozzi et al [17]. In a proof of concept, we assessed whether we could identify putative mastitis pathogens at the species level in random bulk-tank milk samples.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to metabarcoding, the ONT MinION platform has been successfully applied in several studies, including the characterization of bacterial mock communities [25,27,28]; microbiota profiling of species and tissues such as dog skin [29], canine feces [30], equine gut [31], water buffalo milk [32], sea louse [33], and microalgae [34]; identification of fungi [35]; and characterization of plastic-associated species in the Mediterranean sea [36]. Additionally, metagenetic analyses of environmental samples obtained from glacial regions [37], aquatic environments (e.g., ocean water column [38], river water [39], wastewater [40], and freshwater [41]), building dust [22], and the International Space Station [42] demonstrate the potential and applicability of nanopore sequencing for microorganism detection across diverse environments and field settings.…”
Section: Introductionmentioning
confidence: 99%